Total care expenditures and their drivers among older adults: A study on health and long-term care expenditures in South Korea - Hyo Young Lee; Young-Ran Chin (BMC, 2022)
Abstract Background South Korea operates two different national insurance systems: health care insurance covers medical services and long-term care (LTC) insurance covers residential care and home care services. Total care expenditures include benefits from both these insurance schemes and personal payments made for receiving these services. This study aims to identify total care expenditures per older person along with related factors and their effects on care expenditures. Methods We analyzed claims data of 2017 for LTC and health care insurance in Korea using multiple regression analysis. Participants were recipients of LTC insurance, aged 60 years or above (n = 650,059). The variables of interest included socioeconomic characteristics, disabilities, chronic diseases, and care needs levels. Results The total expenditures were approximately USD 9,808,922,016 for 650,059 older people (USD 15,089.28 ± 8,006.57 per person) in 2017. The benefits of national health insurance accounted for 86.03% of the total, while personal payments accounted for 13.97%. Comparing the expenditure across services, the total amount was found to be much higher for LTC services. The personal payments were similar for the two insurance schemes, and the proportion of expenses by service type (to total expenses) was greater for LTC (LTC versus health care expenditures: 63.25% versus 36.15% of the total expenditures). The total care expenditures differed significantly according to recipient characteristics. Older adults who were women, between 75-84 years old, with higher care needs levels, and who suffered from diseases and lived in the residential facilities were associated with an increase in total expenditures. Moreover, factors such as any type of disability and living alone were related to a decrease in total care expenditures. Conclusions The increase in care expenditures should be monitored from an integrated perspective on overall health care and LTC, and to reduce care needs. In addition, we should focus on the factors involved in using (receiving) services for older individuals and complementing the lack of or inadequate services to enhance and sustain the LTC and health care service systems. Older adults receiving full basic livelihood security and living alone should receive greater attention from the perspective of social equity.